English Professors’ Competences: A View from Universidad Nacional, Costa Rica - Carranza-Marchena, Priscilla (2024)
Mastering English is an essential requirement for the professionals of the 21st century. Therefore, Costa Rican public universities, and specifically, Universidad Nacional (UNA) must ensure an adequate and efficient pedagogical praxis from the English as a Foreign Language professors in terms of a) academic competences, b) language competences, c) competences to address diversity and inclusion, d) pedagogical mediation, e) competences in evaluation, and f) technological competences. This article problematizes, from a personal perspective, the principles previously mentioned in relation to university teaching; thus, it discusses the identified possible pedagogical paths to face the challenges of these contemporary times.